Molecular insights from dysregulation of the thiazide‐sensitive WNK/SPAK/NCC pathway in the kidney: Gordon syndrome and thiazide‐induced hyponatraemia. (December 2013) - Glover, Mark; O'Shaughnessy, Kevin M
Summary Human blood pressure is dependent on balancing dietary salt intake with its excretion by the kidney. Mendelian syndromes of altered blood pressure demonstrate the importance of the distal nephron in this process and of the thiazide‐sensitive pathway in particular. Gordon syndrome (GS), the phenotypic inverse of the salt‐wasting Gitelman syndrome, is a condition of hyperkalaemic hypertension that is reversed by low‐dose thiazide diuretics or a low‐salt diet. Variants within at least four genes [i.e. with‐no‐lysine(K) kinase 1 (WNK1), WNK4, kelch‐like family member 3 (KLHL3) and cullin 3 (CUL3)] can cause the phenotype of GS. Details are still emerging for some of these genes, but it is likely that they all cause a gain‐of‐function in the thiazide‐sensitive Na+–Cl− cotransporter (NCC) and hence salt retention. Herein, we discuss the key role of STE20/sporulation‐specific protein 1 (SPS1)‐related proline/alanine‐rich kinase (SPAK), which functions as an intermediary between the WNKs and NCC and for which a loss‐of‐function mutation produces a Gitelman‐type phenotype in a mouse model. In addition to Mendelian blood pressure syndromes, the study of patients who develop thiazide‐induced‐hyponatraemia (TIH) may give further molecular insights into the role of the thiazide‐sensitive pathway for salt reabsorption. In the present paper we discuss the key features of TIH, including its high degree of reproducibility on rechallenge, possible genetic predisposition and mechanisms involving excessive saliuresis and water retention. Together, studies of Gordon syndrome and TIH may increase our understanding of the molecular regulation of sodium trafficking via the thiazide‐sensitive pathway and have important implications for hypertensive patients, both in the identification of new antihypertensive drug targets and avoidance of hyponatraemic side‐effects.